The Role of Prematurity in Patients With Hemiplegic Cerebral Palsy. (May 2016) - Zelnik, Nathanel; Lahat, Eli; Heyman, Eli; Livne, Amir; Schertz, Mitchell; Sagie, Liora; Fattal-Valevski, Aviva
A multicenter retrospective study was conducted to investigate the perinatal factors, imaging findings and clinical characteristics of hemiplegic cerebral palsy with a particular focus on children born prematurely. Our cohort included 135 patients of whom 42% were born prematurely; 16% were extreme premature infants who were born at 30 weeks or earlier. Nineteen (14%) were twins. Right hemiplegia was slightly more common and accounted for 59% of the patients. Imaging findings of intraventricular hemorrhage and periventricular leukomalacia were more prevalent in premature children whereas stroke, porencephaly, cerebral hemorrhage and cerebral atrophy were more evenly distributed in both term-born and prematurely-born children ( p < 0.01). The overall prevalence of epilepsy in the cohort was 26% with no differences in full-term compared to prematurely-born children. Regardless of the gestational birth age, intellectual deficits were more common in the presence of comorbidity of both hemiplegia and epilepsy ( p < 0.05).